2023
DOI: 10.1097/corr.0000000000002514
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients Reporting Fractures Experience Food Insecurity More Frequently Than the General Population?

Abstract: BackgroundThe economic burden of traumatic injuries forces families into difficult tradeoffs between healthcare and nutrition, particularly among those with a low income. However, the epidemiology of food insecurity among individuals reporting having experienced fractures is not well understood.Questions/purposes(1) Do individuals in the National Health Interview Survey reporting having experienced fractures also report food insecurity more frequently than individuals in the general population? (2) Are specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…However, this remains a grossly underserved area, leaving millions of people at risk for insufficient healing and poor outcomes. 21,95 Even people who are better resourced at baseline, or those who have less severe trauma, may be challenged by the vast social and economic consequences of an acute injury. 92,93 The injury poses a sudden, unplanned change to life.…”
Section: Recreational Drug Usementioning
confidence: 99%
See 1 more Smart Citation
“…However, this remains a grossly underserved area, leaving millions of people at risk for insufficient healing and poor outcomes. 21,95 Even people who are better resourced at baseline, or those who have less severe trauma, may be challenged by the vast social and economic consequences of an acute injury. 92,93 The injury poses a sudden, unplanned change to life.…”
Section: Recreational Drug Usementioning
confidence: 99%
“…However, this remains a grossly underserved area, leaving millions of people at risk for insufficient healing and poor outcomes. 21,95…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity is associated with malnutrition in older patients [16], which has important implications, because malnutrition has been linked to a higher risk of complications in patients with musculoskeletal conditions [14]. Recent reports have suggested that patients who have experienced orthopaedic trauma may be at increased risk of food insecurity compared with the national mean [7,8,18]. This may be in part because of the socioeconomic implications that sustaining a traumatic orthopaedic injury has on a patient, including temporary or permanent loss of employment and wages and decreased mobility.…”
Section: Introductionmentioning
confidence: 99%
“…But every once in awhile, they’re not. In this month’s Editor’s Spotlight, I’m excited to share a wonderful paper [6] on a topic that—despite its fairly profound importance—I’ve never seen studied in an orthopaedic journal before.…”
mentioning
confidence: 99%
“…A fairly shocking paper in this month’s Clinical Orthopaedics and Related Research ® found that almost one in five patients with fractures also experience food instability [6]. Food insecurity in the United States overall is much less common—closer to one in 10 individuals [10].…”
mentioning
confidence: 99%